Acinetobacter baumannii: Epidemiological and Beta-Lactamase Data From Two Tertiary Academic Hospitals in Tshwane, South Africa - Lowe, Michelle; Ehlers, Marthie M.; Ismail, Farzana; Peirano, Gisele; Becker, Piet J.; Pitout, Johann D. D.; Kock, Marleen M. (Frontiers in Microbiology, 2018)
Acinetobacter baumannii is an opportunistic pathogen that is increasingly responsible for hospital-acquired infections. The increasing prevalence of carbapenem resistant A. baumannii has left clinicians with limited treatment options. Last line antimicrobials (i.e. polymyxins and glycylcyclines) are often used as treatment options. The aim of this study was to determine the prevalence of selected β-lactamase genes from A. baumannii isolates obtained from patients with hospital-acquired infections and to determine the genetic relationship and epidemiological profiles among clinical A. baumannii isolates collected from two tertiary academic hospitals in the Tshwane region, South Africa (SA). Multiplex-PCR (M-PCR) assays were performed to detect selected resistance genes. The collected isolates’ genetic relatedness was determined by using pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). The acquired oxacillinase (OXA) genes, notably blaOXA-23-like were prevalent in the A. baumannii isolates. The M-PCR assays showed that the isolates collected from hospital A contained the OXA-23-like (96%; n=69/72) genes and the isolates collected from hospital B contained the OXA-23-like (91%; n=63/69) and OXA-58-like (4%; n=3/69) genes. Colistin resistance was found in 1% of the isolates (n=2/141) and tigecycline intermediate resistance was found in 6% of the isolates (n=8/141). The A. baumannii isolates were genetically diverse. Molecular epidemiological data showed that specific sequence types (STs) (ST106, ST229, ST258 and ST208) were established in both hospitals, while ST848 was established in hospital A and ST502, ST339 and the novel ST1552 were established in hospital B. ST848 (established in hospital A) was predominately detected in ICU wards whereas ST208, ST339 and the novel ST1552 (established in hospital B) were established in ICUs and the general wards. The origin of the A. baumannii isolates in the hospitals may be due to the dissemination and adaptation of a diverse group of successful clones. Poor infection control and prevention strategies and possibly the overuse of antimicrobials contributed to the establishment of these A. baumannii clones in the studied hospitals.